1997
DOI: 10.3109/00016489709113471
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attachment of β-Haemolytic Streptococci Group A to Oropharyngeal Epithelium in Health and Disease

Abstract: Localization and semiquantification of beta-haemolytic streptococci, Group A (GABHS), GABHS attachment and general bacterial attachment to epithelial cells (bacterial number and morphology) were studied during GABHS-positive acute tonsillitis and pharyngitis infections and among healthy GABHS carriers. Samples were collected from various areas of the oropharynx (palatine tonsils, posterior oropharyngeal wall, palatoglossal arch and buccal mucosa). During acute tonsillitis and pharyngitis, GABHS grew in samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…are very common problems in infectious disorders during childhood [1,2]. In the United States, by 3 years of age more than 80% of children have had at least one episode of AOM, and by 7 years of age, almost 40% of children have had six or more episodes of AOM [3].…”
mentioning
confidence: 99%
“…are very common problems in infectious disorders during childhood [1,2]. In the United States, by 3 years of age more than 80% of children have had at least one episode of AOM, and by 7 years of age, almost 40% of children have had six or more episodes of AOM [3].…”
mentioning
confidence: 99%
“…By using refined methods, and taking advantage of immunofluorescence and immunocytochemical techniques, there are better prospects of elucidating the intial stages of AT etiopathogenesis. Recently, we showed that S. pyogenes microorganisms have a definite affinity for the epithelium covering lymphatic tissue [8]. Moreover, we showed that S. pyogenes colonies were remarkably increased in number in relation to other aerobic colonies on the tonsillar surfaces during an AT infection.…”
Section: Discussionmentioning
confidence: 81%
“…to the surface epithelium, as has been suggested recently [4,8,9]. Attachment of pathogenic bacteria to tonsillar epithelium could only be recognized during an on-going AT infection, but not among healthy carriers of S. pyogenes [8]. The first essential stage in the etiopathogenesis of AT must therefore be the penetration of the mucous film covering the palatine tonsils.…”
Section: Tem Studiesmentioning
confidence: 90%
“…Several reports have demonstrated increased attachment of S. pyogenes to tonsillar or pharyngeal epithelium during acute tonsillitis [2]. Local immunity may be one of the host factors that inhibits bacterial adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adhesion to tonsillar or pharyngeal epithelium may be a potential cause of this recurrent phlogistic condition [1,2]. Humoral immunity of the host may be an another cause of recurrent tonsillitis (RT).…”
Section: Introductionmentioning
confidence: 99%